47‐4: Invited Paper: Flexible AMOLED based on Oxide TFT with High Mobility. Issue 1 (May 2016) - Xu, Hua; Li, Min; Wang, Lei; Xu, Miao; Ning, Honglong; Peng, Junbiao
Abstract : We report a flexible AMOLED display driven by oxide thin film transistors (TFTs) based on a polyimide (PI) substrate. In the oxide TFT, a triple‐stacked structure of active layer is employed to improve the mobility and stability. The fabricated TFT exhibit a high field‐effect mobility of 38.8 cm 2 V −1 s −1, a subthreshold swing of 0.15 V/dec, and an Ion /Ioff ratio of 10 9 . Meanwhile, Al2 O3 film prepared by the method of atomic layer deposition (ALD) is used as the encapsulation of AMOLED display, which demonstrating a superior water vapor transmission rate (WVTR) as low as 5.43×10 −5 g/m 2 /day estimated by Calcium (Ca) corrosion method at 40 °C/100%.